Extended axial imaging range, widefield swept source optical coherence tomography angiography - Liu, Gangjun (J Biophotonics, 2017)
We developed a high-speed, swept source OCT system for widefield OCT angiography (OCTA) imaging. The system has an extended axial imaging range of 6.6 mm. An electrical lens is used for fast, automatic focusing. The recently developed split-spectrum amplitude and phase-gradient angiography allow high-resolution OCTA imaging with only two B-scan repetitions. An improved post-processing algorithm effectively removed trigger jitter artifacts and reduced noise in the flow signal. We demonstrated high contrast 3mm×3mm OCTA image with 400×400 pixels acquired in 3 seconds and high-definition 8mm×6mm and 12mm×6mm OCTA images with 850×400 pixels obtained in 4 seconds. A widefield 8mm×11mm OCTA image is produced by montaging two 8mm×6mm scans. An ultra-widefield (with a maximum of 22 mm along both vertical and horizontal directions) capillary-resolution OCTA image is obtained by montaging six 12mm×6mm scans.